Methods for wildlife monitoring in tropical forests: Comparing human observations, camera traps, and passive acoustic sensors. Issue 12 (2nd November 2021) - Zwerts, Joeri A.; Stephenson, P. J.; Maisels, Fiona; Rowcliffe, Marcus; Astaras, Christos; Jansen, Patrick A.; van der Waarde, Jaap; Sterck, Liesbeth E. H. M.; Verweij, Pita A.; Bruce, Tom; Brittain, Stephanie; van Kuijk, Marijke
Abstract: Wildlife monitoring is essential for conservation science and data‐driven decision‐making. Tropical forests pose a particularly challenging environment for monitoring wildlife due to the dense vegetation, and diverse and cryptic species with relatively low abundances. The most commonly used monitoring methods in tropical forests are observations made by humans (visual or acoustic), camera traps, or passive acoustic sensors. These methods come with trade‐offs in terms of species coverage, accuracy and precision of population metrics, available technical expertise, and costs. Yet, there are no reviews that compare the characteristics of these methods in detail. Here, we comprehensively review the advantages and limitations of the three mentioned methods, by asking four key questions that are always important in relation to wildlife monitoring: (1) What are the target species?; (2) Which population metrics are desirable and attainable?; (3) What expertise, tools, and effort are required for species identification?; and (4) Which financial and human resources are required for data collection and processing? Given the diversity of monitoring objectives and circumstances, we do not aim to conclusively prescribe particular methods for all situations. Neither do we claim that any one method is superior to others. Rather, our review aims to support scientists and conservation practitioners in understanding the options and criteria that must be considered in choosing the appropriate method, given the objectives of their wildlife monitoring efforts and resources available. We focus on tropical forests because of their high conservation priority, although the information put forward is also relevant for other biomes. Abstract : Wildlife monitoring is essential for conservation science and data‐driven decision‐making. We compare three commonly used monitoring methods by following four questions that are always important in relation to wildlife monitoring.